ANGI-06. THE MATRIX PROTEIN THROMBOSPONDIN-1 IS A DOWNSTREAM TARGET OF TGF-β INDUCED MICROTUBE FORMATION IN GLIOBLASTOMA. (5th November 2018) - V. Joseph, Justin; Magaut, Capucine; Trones, Amalie; Grosch, Julia; Zhou, Wenjing; Hossain, Jubayer; Abdul Latif, Md; Ninzima, Sandra; AE Kruyt, Frank; Bjerkvig, Rolf; Winkler, Frank; Daubon, Thomas; et al.
Abstract: Microtubes (MTs), which are cytoplasmic extensions of glioma cells, have recently been discovered as important cell communication structures. MTs are abundant in chemoresistant 1p/19q non-codeleted tumors, in particular glioblastomas, however are scarce in chemosensitive 1p/19q co-deleted oligodendrogliomas. Here we report that TGF-β is an important mediator of MT formation. TCGA data analysis revealed upregulation of TGF-β growth-factors and receptors in non-codeleted versus co-deleted tumors. TGF-β stimulation in vitro promotes enhanced MT formation in a panel of GBM stem cell lines which was blocked by a TGFBR2 inhibitor (Ly2157299). Analysis of RNA sequencing data comparing TGF-β stimulated versus unstimulated cells revealed extracellular matrix receptor interactions as a major regulated pathway. We identified Thrombospondin-1 (THBS1) as a major candidate of this pathway, which was upregulated upon TGF-β stimulation in GBM stem cell lines. Interestingly, one GBM stem cell line that did not respond to TGF-β stimulation with enhanced MT formation lacked also upregulation of THBS1. This non-responder cell line did not invade into fetal microbrains in vitro and xenografts in vivo, whereas responder cell lines showed a highly invasive and MT forming phenotype in both models. Knockdown of THBS1 in a responder cell line using shRNAs substantially reduced MT formation in vitro and in vivo. Thus, we identified THBS1 as an important mediator of MT formation downstream of TGF-β, which might play a role in therapy resistance of GBM.